Prevalence and determinants of dental caries among primary school children in urban area of Kancheepuram district, Tamil Nadu: a cross sectional study - M., Arunkumar; S., Gopalakrishnan; R., Uma Devi (International Journal Of Community Medicine And Public Health, 2019)
Background: Dental caries is a preventable multi factorial disease which shows increase in prevalence over last five decades in India. In order to reduce its magnitude and for effective prevention and control, the risk factors and distribution should be well known. This study was planned with the objective of assessing the prevalence and determinants of dental caries among primary school children in an Urban area of Kancheepuram district, Tamil Nadu, India. Methods: This school based cross sectional study was carried out between November 2017 and February 2018 using a sample size of 430 selected from two schools by simple random sampling. Data were collected using a pre-tested, structured questionnaire, which were analyzed using SPSS version 16.0 and presented using descriptive and analytical statistics. Results: Among the study participants, 52.9% had dental caries. Plaque accumulation was noted in 46.2%. About 74% were taking junk foods daily. About 47.1% children were rinsing their mouth daily and 34.6% were brushing more than once daily. Factors found to be protective against dental caries were high socio economic class and daily mouth rinsing habit. Odds of getting dental caries was more among children with visible dental plaque, daily junk foods intake, brushing once daily and failing to brush after foods. Conclusions: Dental caries is a high prevalent, preventable disease affecting both young and old aged individuals that can be mitigated by health education activities. Proper oral hygiene can prevent dental caries. Hence more importance should be given for oral hygiene and behavioral changes in dietary habits.